Pengaruh Perawatan Payudara Terhadap Kelancaran Asi dan Tingkat Kecemasan Pada Ibu Nifas - Junaida Rahmi; Siti Novy Romlah; Amanda Rischa Ramadihina; Indah Purnama Sari (STIKes Kharisma Persada, 2020)
The process of breastfeeding can run ejection if prolactin and oxytocin increase. Prolactin functions to produced milk and at the same time oxytocin is also released in response to stimulation of the nipples. Oxytocin functions for milk expenditure. Many types of methods to stimulate the released of the hormone prolactin and oxytocin are the choices for mothers who experience problems during breastfeeding, such as oxytocin massage, prolactin massage, marmet massage, breast care and so forth. The purpose study is the breast care to the ejection of breast milk and anxiety levels in postpartum mothers. The research design used a quasi experiment with the design of two groups pretest-posttest design that contained pretest before being given treatment and posttest after treatment. Research result Dependent t test results shows there are differences in the ejaction of breast milk before and after breast care in postpartum mothers (p = 0.031), there was no difference in anxiety levels before and after breast care in post partum mothers (p value= 0.278).